ADJUSTABLE CONCERT HALL ACOUSTICS DESIGN STUDY FOR CLASSICAL AND ANGKLUNG MUSIC - Caroline Tambunan, Devina
The environment of a concert hall has specially designed acoustics intended for musical performances. A concert hall with an adjustable concept is applied to accommodate different acoustic requirements of different types of music. The concert hall’s geometrical design, acoustic simulation, and auralization processes were done using CATT-Acoustic v9.1 software. Variations of the concert hall’s configurations were created based on variable reverberation times. In this research, the types of music considered are 3 classical music, specifically romantic, classical, and opera, as well as one of Indonesian traditional music, which is the angklung music. An adjustable concert hall was designed to accommodate the 4 types of music, where 4 configurations were made with different T-15 reverberation time values, which are 2.0 s, 1.7 s, 1.5 s, and 1.3 s at 1 kHz. In addition to T-15, other acoustical parameters considered were C-80, ????????, LF, SPL, G, and IACC, where simulation results of the 4 configurations fulfilled the required range of values for each acoustic parameter for all 4 types of music. The impulse response acquired from the acoustic simulation of the 4 concert hall configurations were used for auralization process, namely pieces composed by Mahler, Beethoven, and Mozart, and an angklung music. Auralizations were used in listening tests to obtain preference from respondents on the 4 types of music towards the designed concert hall configurations using paired comparison method by online questionnaire. Listening tests results showed significance in preference towards configuration III and IV for Beethoven’s piece and configuration IV for the angklung music, meanwhile for the other 2 pieces there were no significant preference towards any of the configurations. Based on the analysis done, it was known that respondents’ preferences were mainly affected by the acoustic parameter LF and by the effects of tone coloration, which created shrill sounds in the auralizations.